2020
DOI: 10.1111/wrr.12798
|View full text |Cite
|
Sign up to set email alerts
|

Lesional skin in vitiligo exhibits delayed in vivo reepithelialization compared to the nonlesional skin

Abstract: Vitiligo, a common skin disorder, is characterized by the loss of functional melanocytes resulting in the depigmentation of skin. Previous studies have demonstrated molecular and architectural alterations in the epidermal keratinocytes upon loss of melanocytes. The physiological implications of these "altered" keratinocytes are yet not known. We investigated the wound healing efficiency of lesional vs nonlesional skin in 12 subjects with stable nonsegmental vitiligo using histological and ultrastructural evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Ultrastructural studies on the non‐lesional part of the vitiligo skin report altered keratinocytes, including the presence of extracellular granular material and vacuolar changes in basal keratinocytes associated with epidermal and dermal lymphocyte infiltrates (Moellmann et al, 1982; Hann et al., 1992). Lesional skin has a delayed wound repair (Gupta et al., 2020) and slow recovery kinetics compared with patient‐matched non‐lesional skin (Liu et al., 2010). Additionally, due to the selective loss of melanocytes, keratinocytes in the regions that lack pigment are vulnerable to environmental toxins (Lee et al., 2005).…”
Section: Aging‐induced Dermal and Epidermal Changesmentioning
confidence: 99%
“…Ultrastructural studies on the non‐lesional part of the vitiligo skin report altered keratinocytes, including the presence of extracellular granular material and vacuolar changes in basal keratinocytes associated with epidermal and dermal lymphocyte infiltrates (Moellmann et al, 1982; Hann et al., 1992). Lesional skin has a delayed wound repair (Gupta et al., 2020) and slow recovery kinetics compared with patient‐matched non‐lesional skin (Liu et al., 2010). Additionally, due to the selective loss of melanocytes, keratinocytes in the regions that lack pigment are vulnerable to environmental toxins (Lee et al., 2005).…”
Section: Aging‐induced Dermal and Epidermal Changesmentioning
confidence: 99%
“…We chose the 14th day postwound (instead of the 12th day in our earlier study) to capture another time frame in the process of wound healing and investigate whether L re‐epithelialization finally manages to catch up with the NL skin. Though the L skin in this study exhibited significantly enhanced re‐epithelialization (Day 14) as compared to Day 12 (Gupta et al, 2020), the continued presence of spongiosis and hyperkeratosis (compared to Day 14 NL skin) indicated that the delay in wound healing persists even beyond the 12th day.…”
Section: Discussionmentioning
confidence: 54%
“…We chose the 14th day postwound (instead of the 12th day in our earlier study) to capture another time frame in the process of wound healing and investigate whether L reepithelialization finally manages to catch up with the NL skin. Though the L skin in this study exhibited significantly enhanced reepithelialization (Day 14) as compared to Day 12 (Gupta et al, 2020) (Banerjee & Sen, 2015;Schneider, 2012;Singhvi et al, 2018). For instance, miR-146a and miR-155 influence the inflammatory cascade by promoting the production of cytokines and growth factors necessary for the differentiation of monocytes into macrophages (Essandoh et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations